Comparison of Diagnostic Value of the SARC-F and Its Four Modified Versions in Polish Community-Dwelling Older Adults - Krzymińska-Siemaszko R; Deskur-Śmielecka E; Kaluźniak-Szymanowska A; Murawiak M; Wieczorowska-Tobis K (Clinical Interventions in Aging, 2023)
Roma Krzymińska-Siemaszko, Ewa Deskur-Śmielecka, Aleksandra Kaluźniak-Szymanowska, Marika Murawiak, Katarzyna Wieczorowska-Tobis Department of Palliative Medicine, Poznan University of Medical Sciences, Poznan, PolandCorrespondence: Roma Krzymińska-Siemaszko, Department of Palliative Medicine, Poznan University of Medical Sciences, os. Rusa 55, Poznań, 61-245, Poland, Tel/Fax +48 61 8738303, Email romakrzyminska@interia.plPurpose: Sarcopenia is associated with adverse outcomes in elderly persons, including functional disability, falls, and even death. Therefore, older adults should be routinely screened for sarcopenia. Due to the unsatisfactory sensitivity of the SARC-F questionnaire, four modified versions have been elaborated: SARC-CalF, SARC-F+EBM, SARC-F+AC, and SARC-CalF+AC. The diagnostic performance of the four modifications of SARC-F has yet to be compared.Materials and Methods: We performed the sensitivity/specificity analysis and compared the overall diagnostic accuracy of the five questionnaires in 260 community-dwelling volunteers aged ≥ 60 yrs from Poland. The study was performed against three reference standards: the European Working Group on Sarcopenia in Older People (EWGSOP1), EWGSOP2, and modified EWGSOP2 criteria.Results: The prevalence of sarcopenia based on these criteria was 20.8%, 11.2%, and 17.3%, respectively. Concerning the three reference standards, the sensitivity of SARC-F, SARC-CalF, SARC-F+EBM, SARC-F+AC, and SARC-CalF+AC ranged from 31.5– 44.8%, 57.4– 65.5%, 48.1– 62.1%, 71.4– 79.2% and 71.4– 79.2%, respectively. The specificity ranged from 86.6– 87.4%, 86.1– 90.3%, 82.3– 84.0%, 69.4– 78.2%, and 72.1– 79.7%, respectively. The AUCs of SARC-F, SARC-CalF, SARC-F+EBM, SARC-F+AC, and SARC-CalF+AC ranged from 0.643– 0.700, 0.757– 0.792, 0.740– 0.775, 0.767– 0.812 and 0.771– 0.852, respectively.Conclusion: The SARC-F questionnaire has low diagnostic accuracy, which limits its usefulness as a sarcopenia screening tool. Incorporating two simple anthropometric measurements, ie, arm and calf circumference, notably improves the diagnostic performance of SARC-F. Based on our results, SARC-CalF+AC seems to be the best screening tool for sarcopenia screening in community-dwelling older adults.Keywords: sarcopenia, screening, older individuals, ROC analysis